ANALISIS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) MELALUI PENDEKATAN SWOT DALAM MENILAI EFEKTIVITAS DAN EFISIENSI PENGELOLAAN PENDIDIKAN - Istri Purwani Lestari, A.A; Tria Anindita Mutiara Hati, Ni Komang; Gede Agung, Anak Agung; Chindytia; Ni Ketut Shinta Kumala Dewi, Shinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the various internal and external challenges faced by primary schools in implementing School-Based Management (SBM), particularly regarding technological adaptation and educational innovation. This study aims to analyze the implementation of SBM through a SWOT approach to assess the effectiveness and efficiency of educational management at SD Negeri 5 Tonja, Denpasar. A descriptive qualitative method was employed for this research. Data collection techniques included observation, interviews with the principal and teachers, and documentation. The data analysis followed three stages: data reduction, data display, and conclusion drawing, integrated with SWOT matrix analysis. The results indicate that the implementation of SBM at SD Negeri 5 Tonja has been executed well, characterized by participatory program planning and strong collaborative leadership. Internal strengths include strong managerial leadership, highly committed teachers, and active stakeholder support. However, internal weaknesses persist, notably the suboptimal utilization of instructional technology and limited digital competence among teachers. External opportunities include government initiatives for educational digitalization, while rapid technological advancements and school competitiveness present external threats. In conclusion, the implementation of SBM at SD Negeri 5 Tonja is effective and efficient, yet it requires strategic improvement. Formulated strategies include optimizing digital transformation programs, organizing sustainable technological training for teachers, and evaluating digital infrastructure periodically to maintain educational quality and competitiveness.